PERAN E-GOVERNMENT DALAM MEWUJUDKAN TRANSPARANSIPEMERINTAHAN DI PROVINSI SULAWESI TENGGARA - Sri Hadijah Arnus (Institut Agama Islam Negeri Kendari, 2017)
Applying e-government system is the fulfillment of public demands dealing with transparent government system. It is in line with the application of freedom of information act that allows society to access the government information. This study aims to analyze the public response toward the application of e-government, the roles of e-government in fostering transparent government in Southeast Sulawesi, and the constraints faced by Bureau of Public Relations and PDE as the manager of e-government in this regioni. The findings indicated that there was still lack of information to publics about the existence of e-government in Southeast Sulawesi. The information and data presented on the website require the ability and understanding of good administrative skill, so that only people who have high levels of education and knowledge who can understand the information and data presented. The government has also implemented e-government system in fostering transparent government. One of them is online-based government services system which presents all working plans and the use of development funds in e-government. Meanwhile, there are still a lot of incomplete and inaccurate data and information on the site